Influencia sobre las nuevas generaciones de Spodoptera frugiperda provenientes de larvas tratadas con Imidacloprid y Lambdacialotrina - Balarezo Casa, Carlos Alberto (2015)
The present research was conducted at the experimental farm "San Pablo" of the Faculty of Agricultural Sciences at the Technical University of Babahoyo. It is located at Km 7.5 via Babahoyo – Montalvo; data collection and observations performed in the Laboratory of Entomology located at the Faculty, to define the fecundity and fertility of female S. frugífera collected in the Babahoyo. Larvae were taken in the development process, he took them to the laboratory and here their life cycle thereby obtaining egg masses to start the work was completed. When the egg masses hatched larvae they were separated in feeding them individual cups with pieces of tender leaves of corn, and placing pieces of damp cotton with distilled water to provide adequate humidity, until they reached the third instar which proceeded to the implementation of imidacloprid at doses of 335 μg/drop and Lambda-cyhalothrin at dose of 6 μg/drop.........